Synthesis, HPLC analysis and biological activity of dynamic polymyxin - Martynov, Artur; Sklyar, Nadiya; Farber, Boris (Annals of Mechnikov's Institute, 2022)
The peptide antibiotic polymyxin is one of the last line drugs in the fight against resistant forms of microorganisms. Although polymyxin has been known as an antibiotic for more than 40 years, resistance to it in microorganisms has developed rather slowly. To date, the emergence of resistant strains has accelerated exponentially. To date, the emergence of resistant strains has accelerated exponentially. With the calculated degree of modification, a mixture of more than 16,000 polymyxin derivatives is obtained, which interact in solution with each other to form complex supramolecular self-organizing structures and have the properties of adaptation to the microorganism. Thus, the aim of the work was to synthesize dynamic succinyl-maleinyl-acetyl-polymyxin, confirm the change in its structure using reverse-phase high-performance liquid chromatography (RP-HPLC), determine the MIC and MBC for the dynamic structure on the example of two strains of Pseudomonas aeruginosa - ATCC strain and polymyxin-resistant hospital strain. Materials and methods. polymyxin B (I) is dissolved in 10 ml of dioxane, 287 μM succinic anhydride (III), acetic anhydride (II), maleic anhydride are added, the solution is stirred and heated under reflux for 10 minutes. The solution was poured into ampoules and lyophilized to remove solvent and acetic acid. The combinatorial mixture (IVa-d) is used to obtain pharmaceutical compositions, study the structure, determine the biological activity. The HPLC equipment consisted of Milichrom A-02 HPLC. The LC column was ProntoSIL 120-5 C18 AQ. A gradient mobile phase was employed: phase A: [4M LiClO4 – 0,1M HClO4]: H2O=1:19; and phase B: 100% CH3CN were used. Multiwave UV detector was used for detection of fractions. The antimicrobial activity of the compounds was studied in a collection of test strains of microorganisms obtained from the Institute of Microorganisms Museum and living culture museums of various laboratories of the IMI NAMS (Kharkov). The collection included the following multiresistant strains: bacteria - Pseudomnas aeruginosa IMI Res3 and P. aeruginosa ATCC 27853. For the cultivation of bacteria, Mueller-Hinton broth (pH 7.2-7.4) was used. Antimicrobial activity was evaluated by the minimum inhibitory concentration (MIC) - the smallest amount of a substance that completely inhibited the growth of bacteria or fungi after cultivation. IPC was determined by the conventional method of serial dilutions with a coefficient of 2 in a liquid nutrient medium. For this purpose, the initial dilution of the test compound with a concentration of 50 μg / ml of culture medium (MH broth) was prepared. Subsequently, a sequential double dilution was carried out, as a result of which 25 ml were contained in 1 ml of culture medium; 12.5; 6.25; 3.12 μg/mL, etc. Results and discussion. After dynamization of the polymyxin structure, the absorption peaks of all components shift and expand. The 4th and 5th absorption peaks of a main components are slightly shifted to the hydrophobic region, which indicates the completion of the chemical reaction of structure modification. At the same time, complete separation into individual derivatives is not observed, probably due to the very similar molecular masses and charges of these derivatives and their large number (16383 components). Conclusion. For the first time, a dynamic supramolecular succinyl-maleinyl-acetyl-polymyxin (IV) was synthesized, its containing 16383 minor components of various derivatives. It has been shown that the synthesized dynamic polymyxin (IV) is more hydrophobic than the original polymyxin (I) molecule. MIC (IV) for both the resistant strain of P. aeruginosa and for the standard strain P.aeruginosa ATCC 27853 was 3.12 µg/mL, while the original (I) was active only against P.aeruginosa ATCC 27853 and amounted to 6, 25 µg/mL MBC (IV) for both experimental strains of P. aeruginosa coincided and amounted to 6.25 µg/mL, while MBC (I) was 12.5 µg/mL, and the original polymyxin (I) was ineffective for the resistant strain P. aeruginosa